Solid catalyst for polypropylene production and method for producing block copolymer
By using Ziegler catalyst system with magnesium, titanium, halogen and internal electron donors in polypropylene polymerization, combining alkylaluminum compounds and silane compounds as external electron donors, the problems of insufficient catalyst activity and insufficient rubber content in the prior art were solved, and block copolymer production with high three-dimensional regularity and high rubber content was achieved.
Patent Information
- Application Number
- CN202411275669.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-18
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-18
AI Technical Summary
It is difficult to produce block copolymers with high three-dimensional regularity and high rubber content in the prior art, and the catalyst activity is not sufficient to meet the impact strength and processability requirements of automotive interior and exterior materials.
A catalyst system is used, which includes Ziegler catalysts of magnesium, titanium, halogen and inner electron donors as the main catalyst components, an alkylaluminum compound as the cocatalyst, and a tetraalkoxysilyl compound and a dialkoxysilyl compound or a trialkoxysilyl compound as the outer electron donor.
By using this catalyst system, the three-dimensional regularity and rubber content of propylene polymer can be significantly improved, the impact strength and processability of the polymer can be enhanced, and the needs of automotive interior and exterior decoration materials can be met.
Smart Images

Figure CN119638872A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid catalyst for producing polypropylene and a method for producing a block copolymer, in particular to a solid catalyst for producing polypropylene having high activity and excellent hydrogenation activity, which can produce a block copolymer having high stereoregularity and high rubber content through the copolymerization reaction of α-olefins, and a method for producing the block copolymer. Background Art
[0002] The content described below merely provides background information related to the present disclosure and does not constitute prior art.
[0003] Polypropylene is a very useful material in daily life or commercial applications. It is particularly widely used not only in household items such as food containers, but also in automobiles and electronic products. In order to improve the performance of polypropylene in various products, it is very important to enhance its rigidity by increasing its crystallinity.
[0004] At the same time, the impact strength required for automotive interior and exterior materials can be met by producing block copolymers containing high propylene rubber, and for this purpose, the role of the polymerization catalyst needs to be clarified. This means that the polymer produced by the polymerization reaction using the catalyst should have high rigidity due to its high stereoregularity, and should also have high copolymerization ability with α-olefins to meet the requirements of impact strength, processability, etc. To this end, it is necessary to appropriately select the carrier, internal electron donor and external electron donor, which constitute the Ziegler-Natta propylene polymerization (PP) catalyst system. Most of the drastic changes strongly tend to be determined by the carrier and internal electron donor that constitute the Ziegler-Natta PP catalyst system, but the external electron donor is also an important factor supporting the propylene polymerization (PP) reaction. Therefore, even if the same carrier and internal donor are used, not only the activity of the catalyst can be adjusted, but also the copolymerization of α-olefins can be adjusted according to the external electron donor used.
[0005] The external electron donor improves the stereoregularity of the resulting polymer product by selectively poisoning or converting the irregular active sites present on the surface of the solid catalyst. Depending on the molecular structure of the external electron donor used, not only the stereoregularity and molecular weight distribution of the resulting polypropylene change, but also the activity of the catalyst changes. In addition, in the polypropylene copolymer containing the comonomer, the content of the comonomer in the copolymer affects the physical properties of the copolymer.
[0006] Korean Patent No. KR1639497B1 proposes a method for improving the randomness of polymer chains in random copolymers of propylene and comonomers. Korean Patent No. KR1764561B1 discloses a method for making propylene-ethylene copolymers have high transparency and low melting point. However, the above patents do not show block copolymers containing high rubber content, so it is necessary to provide an improved method for producing block copolymers with high rubber content.
[0007] [Existing technical documents]
[0008] 1.KR1639497B1
[0009] 2.KR1764561B1 Summary of the invention
[0010] The present disclosure aims to solve the above-mentioned problems occurring in the prior art, and the object of the present disclosure is to provide a catalyst system which does not adversely affect the catalytic activity, has high propylene polymerization activity, and can increase the rubber content, and to provide a method for producing a block copolymer.
[0011] The present disclosure provides a method for producing a propylene polymer or a propylene-based copolymer using a catalyst system, wherein the catalyst system comprises:
[0012] (A) a Ziegler catalyst comprising magnesium, titanium, a halogen and an internal electron donor as a main catalyst component;
[0013] (B) as a co-catalyst, an alkylaluminum compound; and
[0014] (C) as external electron donors, (a) at least one tetraalkoxysilyl compound, and (b) at least one dialkoxysilyl compound or at least one trialkoxysilyl compound.
[0015] Specifically, the tetraalkoxysilyl compound may be an alkoxysilyl compound as shown in the following chemical formula 1, the trialkoxysilyl compound may be a compound as shown in the following chemical formula 2, and the dialkoxysilyl compound may be a compound as shown in the following chemical formula 3:
[0016] [Chemical formula 1]
[0017]
[0018] [Chemical formula 2]
[0019]
[0020] [Chemical formula 3]
[0021]
[0022] In the above Chemical Formulas 1 to 3, R1, R2, R3 and R4 are each independently an alkyl group having 1 to 12 carbon atoms, an allyl group having 6 to 20 carbon atoms, or a cycloalkyl group having 3 to 20 carbon atoms, provided that R1, R2, R3 and R4 are not completely the same.
[0023] More specifically, the dialkoxysilane compound represented by Chemical Formula 3 may be dicyclopentyldimethoxysilane (DCPDMS).
[0024] Preferably, as the external electron donor (C), at least one tetraalkoxysilyl compound (a) and at least one dialkoxysilyl compound or at least one trialkoxysilyl compound (b) are mixed together in a molar ratio of 1:0.1 to 20. In this case, the catalyst system can show higher hydrogenation activity, and a block copolymer having better stereoregularity and higher rubber content can be produced by copolymerizing α-olefins using the catalyst system.
[0025] Specifically, the main catalyst component may include 5 to 40 wt % of magnesium, 0.5 to 10 wt % of titanium, 50 to 85 wt % of halogen, and 0.5 to 30 wt % of an internal electron donor.
[0026] Specifically, the internal electron donor may be one or more selected from the group consisting of the following chemical formulae 4 to 12:
[0027] [Chemical formula 4]
[0028]
[0029] [Chemical formula 5]
[0030]
[0031] [Chemical formula 6]
[0032]
[0033] [Chemical formula 7]
[0034]
[0035] [Chemical formula 8]
[0036]
[0037] [Chemical formula 9]
[0038]
[0039] [Chemical formula 10]
[0040]
[0041] [Chemical formula 11]
[0042]
[0043] [Chemical formula 12]
[0044]
[0045] In the above chemical formulas 4 to 12, R5, R6, R7, R8, R9 and R 10 Each is independently an alkyl group having 1 to 15 carbon atoms, an allyl group having 1 to 15 carbon atoms, or a cycloalkyl group having 1 to 15 carbon atoms.
[0046] More specifically, the co-catalyst may be an alkyl aluminum compound represented by the following Chemical Formula 13:
[0047] [Chemical formula 13]
[0048]
[0049] In the above Chemical Formula 13, R is an alkyl group having 1 to 7 carbon atoms.
[0050] Preferably, the molar ratio of aluminum atoms in the co-catalyst to titanium atoms in the main catalyst component may be in the range of 1 to 1,000. In this case, a block copolymer having a higher rubber content can be produced by copolymerizing α-olefin using the catalyst system.
[0051] Preferably, the molar ratio of silicon atoms in the external electron donor to titanium atoms in the main catalyst component may be in the range of 0.1 to 500. In this case, a block copolymer having a higher rubber content can be produced by copolymerizing α-olefin using the catalyst system.
[0052] Furthermore, the embodiments of the present disclosure may provide a propylene polymer or copolymer produced by the above-mentioned production method.
[0053] The present disclosure may also provide a catalyst system for producing a propylene polymer or a propylene-based copolymer, the catalyst system comprising:
[0054] (A) a Ziegler catalyst comprising magnesium, titanium, a halogen and an internal electron donor as a main catalyst component;
[0055] (B) as a co-catalyst, an alkyl aluminum compound;
[0056] (C) as external electron donors, (a) at least one tetraalkoxysilyl compound, and (b) at least one dialkoxysilyl compound or at least one trialkoxysilyl compound.
[0057] Embodiments of the present disclosure may provide a catalyst system in which the tetraalkoxysilyl compound is an alkoxysilyl compound represented by the following Chemical Formula 1, the trialkoxysilyl compound is a compound represented by the following Chemical Formula 2, and the dialkoxysilyl compound is a compound represented by the following Chemical Formula 3:
[0058] [Chemical formula 1]
[0059]
[0060] [Chemical formula 2]
[0061]
[0062] [Chemical formula 3]
[0063]
[0064] In the above Chemical Formulae 1 to 3, R1, R2, R3 and R4 are as defined above with respect to the method for producing a propylene polymer or a propylene-based copolymer.
[0065] The embodiment of the present disclosure may provide a catalyst system wherein as an external electron donor (C), at least one tetraalkoxysilyl compound (a) and at least one dialkoxysilyl compound or at least one trialkoxysilyl compound (b) are mixed together in a molar ratio of 1:0.1 to 20.
[0066] According to the present disclosure, not only polypropylene having excellent stereoregularity can be produced using a catalyst system having excellent hydrogenation activity, but also a block copolymer having a high rubber content can be produced by copolymerizing α-olefin using the catalyst system. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 is a graph showing the ethylene-propylene rubber (EPR) content according to Example 3, Example 4, Comparative Example 2, and Comparative Example 3 as shown in Table 2 below. DETAILED DESCRIPTION
[0068] The present disclosure will be described in detail through the following examples and comparative examples, but the present disclosure is not limited thereto.
[0069] [Example 1]
[0070] [Production of main catalyst component]
[0071] In a 1-liter glass reactor fully replaced with nitrogen and equipped with a stirrer, 200 ml of toluene and diethoxymagnesium (25 g, 0.219 mol) were added and stirred at 250 rpm while maintaining a temperature of 10°C. 75 ml of titanium tetrachloride was added within 30 minutes, and then the temperature of the reactor was increased to 110°C at a rate of 0.5°C per minute. During the temperature increase, when the temperature reached 25°C, 7.5 ml (0.028 mol) of diisobutyl phthalate (DIBP) was added. The resulting product was reacted at 110°C for 1 hour, and then stirring was stopped to allow the solid product to precipitate. Next, the supernatant was removed, and the remaining solid product was first washed with 250 ml of fresh toluene for 15 minutes, and then further washed.
[0072] Specifically, the solid product obtained as described above was first washed once with 250 ml of fresh toluene at 100° C., and then washed six times with 250 ml of n-hexane at 40° C. each time to obtain a pale yellow solid procatalyst component. The solid procatalyst component was dried under flowing nitrogen for 8 hours, and the titanium content in the obtained solid procatalyst component was 2.9wt%.
[0073] [Propylene homopolymerization]
[0074] In a 4-liter stainless steel high-pressure reactor, 10 mg of a catalyst, 6.6 mmol of triethylaluminum, 0.33 mmol of dicyclopentyldimethoxysilane (DCPDMS) and 0.33 mmol of tert-butoxytriethoxysilane (TBTES) were introduced as a tetraalkoxysilane compound represented by Chemical Formula 1. Subsequently, 1000 ml of hydrogen and 2.4 liters of liquid propylene were injected in sequence, and polymerization was performed at low temperature for 10 minutes, and then at 70° C. for 2 hours. Afterwards, the reactor temperature was lowered to room temperature, the discharge pipe was opened to reduce the pressure in the reactor, and then the reactor was opened to recover the polymerized propylene polymer.
[0075] The catalytic activity and stereoregularity were analyzed by the following methods.
[0076] 1. Catalytic activity (kg PP / g catalyst) = amount of propylene polymer produced (g) / amount of catalyst introduced (mg).
[0077] 2. Stereoregularity (XS) = wt% of the component dissolved in xylene relative to 100 g of polymer.
[0078] 3. Bulk density (BD) = weight of polymer per volume measured using 100 ml of polymer in an uncompressed state.
[0079] 4. Melt Flow Index (MI) = measured according to ASTM D1238 at 230°C using a 2.16 kg weight.
[0080] 5. Melting point (T m ) = measured using differential scanning calorimetry (DSC).
[0081] [Table 1]
[0082] Propylene homopolymer Comparative Example 1 Example 1 Example 2 Activity (kg PP / g catalyst) 70 69 70 BD(g / ml) 0.43 0.43 0.43 MI(g / 10min@2.16kg) 1.5 1.5 1.7 <![CDATA[T m (℃)]]> 163.4 162.8 162.8 XS (wt%) 1.2 1.4 1.4 Mixing ratio (DCPDMS:TBTES) 1:0 1:1 1:2
[0083] [Comparative Example 1]
[0084] The polymerization experiment was conducted in the same manner as in Example 1, except that only 0.66 mmol of dicyclopentyldimethoxysilane (DCPDMS) was used as the external electron donor. Measurement and analysis were conducted using the above-mentioned measurement and analysis methods for propylene homopolymerization, and the results are shown in Table 1 shown above.
[0085] [Example 2]
[0086] Polymerization experiments were conducted using dicyclopentyldimethoxysilane (DCPDMS) and tert-butoxytriethoxysilane (TBTES) as external electron donors according to the propylene homopolymerization described in Example 1. Measurement and analysis were performed using the above-mentioned measurement and analysis methods for propylene homopolymerization, and the results are shown in Table 1 shown above.
[0087] Referring to Table 1 above, by comparing Comparative Example 1 and Examples 1 to 2 in Table 1, it can be seen that Examples 1 and 2 maintain the properties (including catalytic activity) shown in Comparative Example 1, indicating that changes in the production process do not affect the properties of the propylene homopolymer (or matrix).
[0088] [Propylene block copolymer]
[0089] In a 2.0-liter stainless steel reactor replaced with nitrogen and equipped with a stirrer, 5 mg of any solid catalyst was placed, 6.6 mmol of triethylaluminum and 0.66 mmol of external electron donor were introduced, and then 1.2 liters of liquid propylene and 5000 ml of hydrogen were introduced. After that, prepolymerization was carried out at 20°C for 5 minutes, and then propylene homopolymerization was carried out at 70°C for 40 minutes. After the homopolymerization was completed, the reactor temperature was lowered to room temperature, unreacted monomers were removed, and then ethylene was added to make the molar ratio of ethylene to propylene 2:3. Next, the temperature was raised to 70°C, and additional polymerization was carried out at this temperature for 60 minutes, thereby producing a propylene-based block copolymer.
[0090] The catalytic activity and EPR were analyzed by the following methods.
[0091] 1. Catalytic activity (kg PP / g catalyst) = amount of propylene polymer produced (g) / amount of catalyst introduced (mg).
[0092] 2. Ethylene-propylene rubber (EPR) content = wt% of the component dissolved in xylene relative to 100 g of the polymer (ethylene content (wt) / polymer mass (wt) x 100).
[0093] 3. Ethylene content in copolymer (B-C2) = Ethylene content measured by analyzing the copolymer using FT-IR (infrared spectroscopy).
[0094] 4. Bulk density (BD) = weight per volume of polymer measured using 100 ml of polymer in an uncompressed state.
[0095] 5. Melting point (T m ) = measured using differential scanning calorimetry (DSC).
[0096] [Table 2]
[0097] Propylene block copolymer Example 3 Example 4 Comparative Example 2 Comparative Example 3 Activity (kg PP / g catalyst) 73.37 67.41 60.89 11.65 BD(g / ml) 0.4482 0.4503 0.4482 0.4314 <![CDATA[T m (℃)]]> 163.4 163.2 163.4 161.0 EPR (wt%) 33.9 38.0 28.4 12.2 B-C2 16.43 20.17 19.85 13.07 Mixing ratio (DCPDMS:TBTES) 2:1 1:1 1:0 - Mixing ratio (DCPDMS:TEOS) - - - 1:1
[0098] [Comparative Example 2]
[0099] Polymerization experiments were conducted according to the propylene block copolymerization described above, but only dicyclopentyldimethoxysilane (DCPDMS) was used as the external electron donor. Measurement and analysis were performed using the measurement and analysis methods described above for propylene homopolymerization, and the results are shown in Table 2 shown above.
[0100] [Comparative Example 3]
[0101] According to the propylene block copolymerization described above, polymerization experiments were carried out, using dicyclopentyldimethoxysilane (DCPDMS) and tetraethyl orthosilicate (TEOS) as external electron donors. The above-mentioned measurement and analysis methods for propylene homopolymerization were used for measurement and analysis, and the results are shown in Table 2 shown above.
[0102] [Examples 3 and 4]
[0103] According to the propylene block copolymerization described above, polymerization experiments were carried out, using dicyclopentyldimethoxysilane (DCPDMS) and tert-butyltriethoxysilane (TBTES) as external electron donors. In Examples 3 and 4, DCPDMS and TBTES were mixed together in different proportions. Measurement and analysis were carried out using the above-mentioned measurement and analysis method for propylene homopolymerization, and the results were shown in Table 2 shown above. With reference to Table 2, it can be seen that the catalytic activity of Examples 3 and 4 is better than that of Comparative Examples 2 and 3. This result means that an external electron donor without C3 and S4 symmetry should be selected. In other words, when perfect symmetry is broken, the coupling mode between the external electron donor and the carrier may become diversified, and by introducing quaternary butoxide, such as TBTES, the electron density can be increased. This increased electron density and diversified coupling mode are believed to be able to achieve stronger electron supply, thereby improving the activity of the catalyst. However, the result of this phenomenon may vary depending on the characteristics of the internal electron donor mixed with the external electron donor.
[0104] Meanwhile, regarding EPR, referring to Table 2, it can be seen that the EPR of Examples 3 and 4 is superior to that of Comparative Examples 2 and 3. This means that in Examples 3 and 4, the propylene-based block copolymers have a higher ethylene content, thus increasing the rubber content.
[0105] at the same time, Figure 1 is a graph comparing the rubber content between Examples 3 and 4 and Comparative Examples 2 and 3 of the present disclosure.
[0106] refer to Figure 1 , it can be seen that the rubber (EPR) content of Examples 3 and 4 is higher than that of Comparative Example 2. These results show that the rubber content of Example 4 is higher than that of Comparative Examples 2 and 3.
[0107] The above description is only used to illustrate the present disclosure, and those skilled in the art will appreciate that various modifications can be made without departing from the essential features of the present disclosure. Therefore, the embodiments disclosed in this specification are for illustrative purposes rather than limiting the present disclosure, and the spirit and scope of the present disclosure are not limited by these embodiments. The scope of protection of the present disclosure shall be defined by the attached claims, and all equivalent technologies shall be interpreted as being included in the scope of rights of the present disclosure.
Claims
1. A method for producing a propylene polymer or a propylene-based copolymer using a catalyst system, wherein the catalyst system comprises: (A) a Ziegler-type catalyst comprising magnesium, titanium, a halogen and an internal electron donor as a main catalyst component; (B) as a co-catalyst, an alkyl aluminum compound; and (C) as external electron donors, (a) at least one tetraalkoxysilyl compound, and (b) at least one dialkoxysilyl compound or at least one trialkoxysilyl compound.
2. The method according to claim 1, wherein the tetraalkoxysilyl compound is an alkoxysilyl compound represented by the following chemical formula 1, the trialkoxysilyl compound is a compound represented by the following chemical formula 2, and the dialkoxysilyl compound is a compound represented by the following chemical formula 3: [Chemical formula 1] [Chemical formula 2] [Chemical formula 3] wherein R1, R2, R3 and R4 are each independently an alkyl group having 1 to 12 carbon atoms, an allyl group having 6 to 20 carbon atoms, or a cycloalkyl group having 3 to 20 carbon atoms, provided that R1, R2, R3 and R4 are not all the same.
3. The method of claim 1, wherein: As the external electron donor (C), the at least one tetraalkoxysilyl compound (a) and the at least one dialkoxysilyl compound or at least one trialkoxysilyl compound (b) are mixed together in a molar ratio of 1:0.1 to 20.
4. The method of claim 1, wherein the procatalyst component comprises 5 to 40 wt% of magnesium, 0.5 to 10 wt% of titanium, 50 to 85 wt% of halogen, and 0.5 to 30 wt% of internal electron donor.
5. The method of claim 1, wherein the internal electron donor is one or more selected from the group consisting of the following chemical formulas 4 to 12: [Chemical formula 4] [Chemical formula 5] [Chemical formula 6] [Chemical formula 7] [Chemical formula 8] [Chemical formula 9] [Chemical formula 10] [Chemical formula 11] [Chemical formula 12] Among them, R5, R6, R7, R8, R9 and R 10 Each is independently an alkyl group having 1 to 15 carbon atoms, an allyl group having 1 to 15 carbon atoms, or a cycloalkyl group having 1 to 15 carbon atoms.
6. The method of claim 1, wherein the co-catalyst is an alkyl aluminum compound represented by the following Chemical Formula 13: [Chemical formula 13] wherein R is an alkyl group having 1 to 7 carbon atoms.
7. The method of claim 1, wherein the molar ratio of aluminum atoms in the co-catalyst to titanium atoms in the main catalyst component is in the range of 1 to 1000.
8. The method of claim 1, wherein the total molar ratio of silicon atoms in the external electron donor to titanium atoms in the main catalyst component is in the range of 0.1 to 500.
9. Propylene polymer or copolymer produced by the process of any one of claims 1 to 8.
10. A catalyst system for producing a propylene polymer or a propylene-based copolymer, comprising: (A) a Ziegler-type catalyst comprising magnesium, titanium, a halogen and an internal electron donor as a main catalyst component; (B) as a co-catalyst, an alkyl aluminum compound; and (C) as external electron donors, (a) at least one tetraalkoxysilyl compound, and (b) at least one dialkoxysilyl compound or at least one trialkoxysilyl compound.
11. The catalyst system according to claim 10, wherein the tetraalkoxysilyl compound is an alkoxysilyl compound represented by the following Chemical Formula 1, the trialkoxysilyl compound is a compound represented by the following Chemical Formula 2, and the dialkoxysilyl compound is a compound represented by the following Chemical Formula 3: [Chemical formula 1] [Chemical formula 2] [Chemical formula 3] wherein R1, R2, R3 and R4 are each independently an alkyl group having 1 to 12 carbon atoms, an allyl group having 6 to 20 carbon atoms, or a cycloalkyl group having 3 to 20 carbon atoms, provided that R1, R2, R3 and R4 are not all the same.
12. The catalyst system according to claim 10, wherein As the external electron donor (C), the at least one tetraalkoxysilyl compound (a) and the at least one dialkoxysilyl compound or at least one trialkoxysilyl compound (b) are mixed together in a molar ratio of 1:0.1 to 20.
Citation Information
Patent Citations
Propylene random copolymer
KR101639497B1
Random propylene-ethylene copolymers and process for their preparation
KR101764561B1